Here today… here tomorrow: sustainable digital collections – the Stellenbosch experience. - Seyffert, Mimi (My University, 2013)
The aim of this paper is to share the experiences of Stellenbosch University Library and Information Service in developing a digital collections repository, with specific focus on heritage collections. The Library’s strategic intervention of supporting, developing and contributing to high-level scholarly publication output includes the strategic goal of digitising unique collections within the Library and Information Service. This goal has recently been given new impetus with Stellenbosch University joining the Research Libraries Consortium and benefiting from a Carnegie Corporation of New York grant for the digitisation of heritage collections. The paper will look at the various processes we undertook to realise the aims of the project: from selecting and preparing collections for digitisation, liaising with external service providers, choosing a platform to host the content, making the content accessible and ultimately adding value to the collections. I will also discuss the challenges in keeping the integrity of original heritage collections and not jeopardising their context when transforming hard copy to digital. Finally, the paper will examine the ways in which we as the Library and Information Service ourselves have made investments to make these projects sustainable and to ensure not only the maintenance, but also the growth and further development of our digital collections.
The various processes we undertook to realise the aims of the project.
Keywords: Here today… here tomorrow.